PENGARUH PENGGUNAAN MEDIA SPINDLE BOXES DENGAN METODE MONTESSORI TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 4-5 TAHUN - Andi Sulmi ati; Herman Herman; Angri Lismayani; Fadhilah Afifah (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
This study aims to determine the effect of using Spindle Boxes Media with the Montessori Method on the ability to recognize the concept of numbers of children aged 4-5 years at Telkom Kindergarten Makassar. This research approach used is quantitative with the type of Quasi Exprimental Design Research. Sampling in this study were 20 people, 10 children in the experimental group, 10 children as a control group. Data collection techniques in this study are documentation, tests and observations. The data analysis technique in this consists of descriptive statistical test data and non-parametric analysis using the Wilcoxon Sign Rank Test. Based on the results of the Wilcoxon Sign Rank Test research, the sig value was obtained. (2-tailed) 0.005 <0.05 then H0 is rejected and H1 is accepted, namely there is a difference in the average level of ability to recognize the concept of numbers of children aged 4-5 years at Telkom Kindergarten Makassar. The data from the descriptive statistical test can prove the research hypothesis that has been formulated if there is an average difference in the ability to recognize the concept of numbers of children aged 4-5 years, then H0 is rejected and H1 is accepted, namely there is an effect of using Spindle Boxes media with the Montessori method on the ability to recognize the concept of numbers of children aged 4-5 years at Telkom Kindergarten Makassar.